Polymer-coated hexagonal upconverting nanoparticles: chemical stability and cytotoxicity - Patsula, Vitalii; Mareková, Dana; Jendelová, Pavla; Nahorniak, Mykhailo; Shapoval, Oleksandr; Matouš, Petr; Oleksa, Viktoriia; Konefał, Rafał; Vosmanská, Magda; Machová-Urdziková, Lucia; Horák, Daniel (Frontiers in Chemistry, 2023)
Large (120 nm) hexagonal NaYF4:Yb, Er nanoparticles (UCNPs) were synthesized by high-temperature coprecipitation method and coated with poly(ethylene glycol)-alendronate (PEG-Ale), poly (N,N-dimethylacrylamide-co-2-aminoethylacrylamide)-alendronate (PDMA-Ale) or poly(methyl vinyl ether-co-maleic acid) (PMVEMA). The colloidal stability of polymer-coated UCNPs in water, PBS and DMEM medium was investigated by dynamic light scattering; UCNP@PMVEMA particles showed the best stability in PBS. Dissolution of the particles in water, PBS, DMEM and artificial lysosomal fluid (ALF) determined by potentiometric measurements showed that all particles were relatively chemically stable in DMEM. The UCNP@Ale-PEG and UCNP@Ale-PDMA particles were the least soluble in water and ALF, while the UCNP@PMVEMA particles were the most chemically stable in PBS. Green fluorescence of FITC-Ale-modified UCNPs was observed inside the cells, demonstrating successful internalization of particles into cells. The highest uptake was observed for neat UCNPs, followed by UCNP@Ale-PDMA and UCNP@PMVEMA. Viability of C6 cells and rat mesenchymal stem cells (rMSCs) growing in the presence of UCNPs was monitored by Alamar Blue assay. Culturing with UCNPs for 24 h did not affect cell viability. Prolonged incubation with particles for 72 h reduced cell viability to 40%–85% depending on the type of coating and nanoparticle concentration. The greatest decrease in cell viability was observed in cells cultured with neat UCNPs and UCNP@PMVEMA particles. Thanks to high upconversion luminescence, high cellular uptake and low toxicity, PDMA-coated hexagonal UCNPs may find future applications in cancer therapy.